Admixture analyses and phylogeographic relationships reveal complete genetic distinctiveness of Polish farm and wild red foxes (Vulpes vulpes) and the North American origin of farm‐bred individuals. (13th May 2019) - Zatoń‐Dobrowolska, Magdalena; Mucha, Anna; Morrice, David; Wierzbicki, Heliodor; Moska, Magdalena; Dobrowolski, Maciej
Abstract: A number of studies showed that many mtDNA haplotypes were shared among contemporary farm red foxes bred on different continents and the historical wild red foxes of North American origin. Therefore, in this study, the population genetic structure and phylogeographic relationships of Polish red foxes kept on fur farms and their wild conspecifics were investigated to assess the ancestry of the farm red foxes in Poland. A total of 330 tissue samples (200 from farm foxes and 130 from wild foxes) were used for the genetic analyses. Thirty microsatellite loci and two regions of mtDNA were used to assess the level of admixture between farm‐ and wild red foxes, to construct haplotype networks and create a phylogenetic tree. The genetic structure analysis clearly indicated two genetic clusters as being the most probable number of genetically distinct populations. The fixation index revealed a significant genetic distance between the farm‐ and wild red fox populations ( F ST = 0.27, p < 0.05). Haplotype networks based on frequencies showing relationships between concatenated haplotypes of Polish farm‐ and wild red foxes and the constructed phylogenetic tree clearly indicated two genetically distinct groups. The results of this study provide strong evidence confirming the North American origin of red foxes bred on Polish farms and the genetic distinctiveness of both studied populations.